Good luck bear - Foley, Greg E., 1969- (New York : Viking, 2009)
When Bear's friend Mouse tells him that finding a four-leaf clover means one is lucky, the little bear searches for one, despite the discouraging words of other animals.
Booklist.
2.0
ther animals.
Follett Library Resources
K-3
Keywords: Animals -- Juvenile fiction; Bears -- Juvenile fiction; Fortune -- Juvenile fiction; Animals -- Fiction; Bears -- Fiction; Luck -- Fiction; Animals -- Fiction; Bears -- Fiction; Fate and fatalism -- Fiction